VICTIMS’ EXPERIENCES OF RESTORATIVE MEDIATION: A DEVELOPMENTAL SOCIAL WORK PERSPECTIVE - Steyn, Francois; Lombard, Antoinette (Social Work/Maatskaplike Werk, 2014)
Victim-offender mediation is an expression of restorative justice. The wellbeing of victims of crime is a central feature of restorative justice services. The process of restorative mediation entails all parties, i.e. the victim, the offender, their families and members of the community, voluntarily participating in face-to-face dialogue, where truth-telling enables the offender to take personal responsibility for his/her criminal behaviour (Rainford, 2010). An important outcome of restorative mediation is reaching an agreement regarding the strategies to remedy the wrongdoing. A developmental social work perspective counteracts retributive justice in shifting the intervention focus from individual defect and blame to reform and social change (Midgley, 2010). Developmental social work is embedded in investment strategies in restoring people to full functioning in society (Rainford, 2010). In fact, “social investment, economic participation, empowerment and human investment are relevant to all systems and forms of social work intervention” (Midgley, 2010:12